Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1371/journal.pone.0003186
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Poxviruses by Upper-Room UVC Light in a Simulated Hospital Room Environment

Abstract: In the event of a smallpox outbreak due to bioterrorism, delays in vaccination programs may lead to significant secondary transmission. In the early phases of such an outbreak, transmission of smallpox will take place especially in locations where infected persons may congregate, such as hospital emergency rooms. Air disinfection using upper-room 254 nm (UVC) light can lower the airborne concentrations of infective viruses in the lower part of the room, and thereby control the spread of airborne infections amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 15 publications
6
81
0
Order By: Relevance
“…This decay rate was detected under simulated atmospheric conditions of temperature15.9 ± 0.2°C, relative humidity 65-75%, and light intensity 700 μmol photons·m −2 ·s −1 provided by a halogen lamp with a spectrum simulating sunlight (400-700 nm) (SI Materials and Methods). This result is comparable to previous studies that reported nonmarine viruses can remain infective in the atmosphere for several hours (23)(24)(25)(26). In addition, the half-life of infectious EhV in the ocean under similar prevailing condition is, as expected, much longer, ∼35 h (13).…”
Section: Significancesupporting
confidence: 90%
“…This decay rate was detected under simulated atmospheric conditions of temperature15.9 ± 0.2°C, relative humidity 65-75%, and light intensity 700 μmol photons·m −2 ·s −1 provided by a halogen lamp with a spectrum simulating sunlight (400-700 nm) (SI Materials and Methods). This result is comparable to previous studies that reported nonmarine viruses can remain infective in the atmosphere for several hours (23)(24)(25)(26). In addition, the half-life of infectious EhV in the ocean under similar prevailing condition is, as expected, much longer, ∼35 h (13).…”
Section: Significancesupporting
confidence: 90%
“…For example, for a The Z values for influenza virus were statistically different as a function of RH. These differences showing that influenza aerosols are less susceptible to UV at higher RH than at lower RH have been noted in previous UV susceptibility studies for other organisms (18,19). In climate-controlled, indoor environments, high RH values near 75% may be unusual, but in areas without environmental controls UV effectiveness may decrease in the presence of elevated RH.…”
Section: Discussionsupporting
confidence: 59%
“…Even for the most stable viruses, k is typically of the order of 0.01 min (1 , corresponding to an effective half-life of about one hour (Donaldson, 1973;McDevitt et al, 2008). For most other viruses, the inactivation rate in aerosol is considerably higher (Harper, 1961;Miller et al, 1963;de Jong, 1965;Miller and Artenstein, 1967;Songer, 1967;Akers, 1969;Benbough, 1971;Barlow, 1972;Donaldson, 1972;Akers, 1973;Donaldson and Ferris, 1974).…”
Section: Virusesmentioning
confidence: 99%
“…Experimental data on the survival of viruses show that, on the whole, the inactivation rate becomes higher for all viruses with increasing temperature (Zhdanov and Gaudamovich, 1982a;Zhdanov and Gaudamovich, 1982b;Weber and Stilianakis, 2008). Also, the number of surviving viral particles in aerosol decreases with increased radiation dose that the virus aerosol is exposed to (Jensen, 1964;Zhdanov and Gaudamovich, 1982a;Zhdanov and Gaudamovich, 1982b;Sagripanti and Lytle, 2007;McDevitt et al, 2008). Relative humidity influences the survival of viruses in aerosol differently.…”
Section: Virusesmentioning
confidence: 99%